Histology of Liver and Kidney of Mystus nemurus that immersed with Curcuma xanthorrhiza, ROXB extract - Lubis, Fauzi Ahmad; Riauwaty, Morina; Syawal, Henni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was carried out in November 2013 until January 2014 in the laboratory of Fish Diseases and Parasites, Faculty of Fisheries and Marine Science Riau University Pekanbaru. The purpose of this research was to understand the histological structure of liver and kidney of Mystus nemurus that is immersed with Curcuma xanthorrhiza ROXB extract. The method used in this study was experimental and the histologycal structure of the fish will be analyzed descriptively. The treated fish were immerse in 3 different concentration of Curcuma xanthorrhiza ROXB extract, they were (P1 (0.2 g/L), P2 (0.4 g/L, P3 (0.6 g/L). for five minutes/ day for 30 days period. The negative control were fishes that were not treated with Curcuma xanthorrhiza ROXB extract. The liver showed hemorhage, fatty degenerative and necrosis. The kidney showed necrosis and hemorhage. It was concluded that immersion of fish in Curcuma xanthorrhiza ROXB extract shown histologycal alterations in the tissue of Mystus nemurus.Key words: Mystus nemurus, Curcuma xanthorrhiza ROXB, kidney, liver